Unit Value of Net Asset to Mandatory Privately Managed Pension Funds in Romania during May 2008 - December 2015 - Colomeischi Tudor; Iancu Eugenia (Ovidius University Annals: Economic Sciences Series, 2017)
Since 1990, the public pension system in Romania has started to deal with special problems, inparticular demographic. To these were added and all funds due to lower pension payments. In thiscontext it was introduced in 2007 private pensions. In this article we propose an analysis of how ithas evolved Pillar II mandatory private pensions in Romania in May 2008 - December 2015 interms of net asset value per unit. We considered the annual returns of the net asset value per uniton which they were recorded in Pillar II pension funds during this period.